Implementasi Program BUNDACERDAS sebagai Multimedia Interaktif Edukasi Gizi Ibu Hamil dalam Upaya Pencegahan Stunting - Dasril Aldo; Yohani Setiya Rafika Nur; Adanti Wido Paramadini; Muhammad Zaky Mubarok; Harald Riandi Rantetana Purukan; Muhammad Nazmi Al Faiz (Yayasan Darussalam Bengkulu, 2026)
The main problem faced by partner communities in Muntang Village is the low knowledge of pregnant women related to nutritional fulfillment during pregnancy and the strong influence of myths that are not based on science, which has the potential to increase the risk of stunting. This service activity aims to increase the knowledge and awareness of pregnant women, PKK mothers, and posyandu cadres through the use of interactive multimedia nutrition education. The solution offered is the development and implementation of the BUNDACERDAS application as a digital-based educational media that contains material about the First 1000 Days of Life, the nutritional needs of pregnant women, stunting prevention, and interactive quiz features. The method used is a participatory approach through the stages of observation, socialization, training, implementation, and evaluation. The results of the activity showed an increase in participants' knowledge by an average of 31 percent based on a comparison of pre-test and post-test in 50 participants. In addition, the participants' satisfaction level achieved an average score of 4.6 out of a scale of 5 which was included in the very satisfied category. Thus, this activity has proven to be effective in increasing community nutrition literacy and has the potential to be developed sustainably as a technology-based health education media.